Doppler ultrasound surveillance of recently formed haemodialysis arteriovenous fistula: the SONAR observational cohort study - Richards, J; Summers, D; Sidders, A; Allen, E; Ayaz Hossain, M; Paul, S; Slater, M; Bartlett, M; Lagaac, R; Laing, E; Hopkins, V; Fitzpatrick-Creamer, C; et al. (National Institute for Health and Care Research, 2024)
Background: Arteriovenous fistulas are considered the best option for haemodialysis provision, but as many as 30% fail to mature or suffer early failure. Objective: To assess the feasibility of performing a randomised controlled trial that examines whether, by informing early and effective salvage intervention of fistulas that would otherwise fail, Doppler ultrasound surveillance of developing arteriovenous fistulas improves longer-term arteriovenous fistula patency. Design: A prospective multicentre observational cohort study (the ‘SONAR’ study). Setting: Seventeen haemodialysis centres in the UK. Participants: Consenting adults with end-stage renal disease who were scheduled to have an arteriovenous fistula created. Intervention: Participants underwent Doppler ultrasound surveillance of their arteriovenous fistulas at 2, 4, 6 and 10 weeks after creation, with clinical teams blinded to the ultrasound surveillance findings. Main outcome measures: Fistula maturation at week 10 defined according to ultrasound surveillance parameters of representative venous diameter and blood flow (wrist arteriovenous fistulas: ≥ 4 mm and > 400 ml/minute; elbow arteriovenous fistulas: ≥ 5 mm and > 500 ml/minute). Mixed multivariable logistic regression modelling of the early ultrasound scan data was used to predict arteriovenous fistula non-maturation by 10 weeks and fistula failure at 6 months. Results: A total of 333 arteriovenous fistulas were created during the study window (47.7% wrist, 52.3% elbow). By 2 weeks, 37 (11.1%) arteriovenous fistulas had failed (thrombosed), but by 10 weeks, 219 of 333 (65.8%) of created arteriovenous fistulas had reached maturity (60.4% wrist, 67.2% elbow). Persistently lower flow rates and venous diameters were observed in those fistulas that did not mature. Models for arteriovenous fistulas’ non-maturation could be optimally constructed using the week 4 scan data, with fistula venous diameter and flow rate the most significant variables in explaining wrist fistula maturity failure (positive predictive value 60.6%, 95% confidence interval 43.9% to 77.3%), whereas resistance index and flow rate were most significant for elbow arteriovenous fistulas (positive predictive value 66.7%, 95% confidence interval 48.9% to 84.4%). In contrast to non-maturation, both models predicted fistula maturation much more reliably [negative predictive values of 95.4% (95% confidence interval 91.0% to 99.8%) and 95.6% (95% confidence interval 91.8% to 99.4%) for wrist and elbow, respectively]. Additional follow-up and modelling on a subset (n = 192) of the original SONAR cohort (the SONAR-12M study) revealed the rates of primary, assisted primary and secondary patency arteriovenous fistulas at 6 months were 76.5, 80.7 and 83.3, respectively. Fistula vein size, flow rate and resistance index could identify primary patency failure at 6 months, with similar predictive power as for 10-week arteriovenous fistula maturity failure, but with wide confidence intervals for wrist (positive predictive value 72.7%, 95% confidence interval 46.4% to 99.0%) and elbow (positive predictive value 57.1%, 95% confidence interval 20.5% to 93.8%). These models, moreover, performed poorly at identifying assisted primary and secondary patency failure, likely because a subset of those arteriovenous fistulas identified on ultrasound surveillance as at risk underwent subsequent successful salvage intervention without recourse to early ultrasound data. Conclusions: Although early ultrasound can predict fistula maturation and longer-term patency very effectively, it was only moderately good at identifying those fistulas likely to remain immature or to fail within 6 months. Allied to the better- than-expected fistula patency rates achieved (that are further improved by successful salvage), we estimate that a randomised controlled trial comparing early ultrasound-guided intervention against standard care would require at least 1300 fistulas and would achieve only minimal patient benefit. Trial Registration: This trial is registered as ISRCTN36033877 and ISRCTN17399438. Funding: This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: NIHR135572) and is published in full in Health Technology Assessment; Vol. 28, No. 24. See the NIHR Funding and Awards website for further award information.